Penyutradaraan Dan Editing Dalam Pembuatan Film Animasi 3D Bergenre Action Berjudul â€œBedaâ€ - Mega Pandan Wangi; Muhammad Hanif Taqiuddin (CandraRupa : Journal of Art, Design, and Media, 2019)
The objective to be achieved in this Final Project is to produce an Action Animation 3D Film titled "DIFFERENT". This Final Project will use the theme of Racial Differences or Racism, with stories about conditions that will occur if there continues to be conflict due to differences. This work was made because of the increasing number of cases of racial differences (SARA) that are getting worse and worse. This racial difference occurs mostly because it is motivated by the desires of individuals or groups who want to be the best of other races, individuals or groups. Race is a categorization or grouping of humans based on the physical characteristics of the body. This Final Project will use qualitative research methods using data collection techniques in the form of interviews, literature studies, observations, and existing studies. In this 3D animated film, it will use the back and forth flow, displaying Fantasy stories with action genres and combined with visual effects of digital illusions, focusing on stories between 2 characters namely the main character "N" and the female lead character "Princess" who promised to end the war, lasted 12 minutes. With the creation of this short film, it is hoped that it can add insight into the meaning of racial differences and can respect differences.